Molecular mechanism of positive allosteric modulation of the metabotropic glutamate receptor 2 by JNJ‐46281222. (13th January 2016) - Doornbos, Maarten L J; Pérez‐Benito, Laura; Tresadern, Gary; Mulder‐Krieger, Thea; Biesmans, Ilse; Trabanco, Andrés A; Cid, Jose María; Lavreysen, Hilde; IJzerman, Adriaan P; Heitman, Laura H
Abstract : Background and Purpose: Allosteric modulation of the mGlu2 receptor is a potential strategy for treatment of various neurological and psychiatric disorders. Here, we describe the in vitro characterization of the mGlu2 positive allosteric modulator (PAM) JNJ‐46281222 and its radiolabelled counterpart [ 3 H]‐JNJ‐46281222. Using this novel tool, we also describe the allosteric effect of orthosteric glutamate binding and the presence of a bound G protein on PAM binding and use computational approaches to further investigate the binding mode. Experimental Approach: We have used radioligand binding studies, functional assays, site‐directed mutagenesis, homology modelling and molecular dynamics to study the binding of JNJ‐46281222. Key Results: JNJ‐46281222 is an mGlu2 ‐selective, highly potent PAM with nanomolar affinity ( K D = 1.7 nM). Binding of [ 3 H]‐JNJ‐46281222 was increased by the presence of glutamate and greatly reduced by the presence of GTP, indicating the preference for a G protein bound state of the receptor for PAM binding. Its allosteric binding site was visualized and analysed by a computational docking and molecular dynamics study. The simulations revealed amino acid movements in regions expected to be important for activation. The binding mode was supported by [ 3 H]‐JNJ‐46281222 binding experiments on mutant receptors. Conclusion and Implications: Our results obtained with JNJ‐46281222 in unlabelled and tritiated form further contribute to our understanding of mGlu2 allosteric modulation. The computational simulations and mutagenesis provide a plausible binding mode with indications of how the ligand permits allosteric activation. This study is therefore of interest for mGlu2 and class C receptor drug discovery.